Determinants of Mother's Willingness to Breastfeed Exclusively in the Working Area of Polonia Health Center - Khaira Rahayu; Ayi Darmana; Iman Muhammad (International Archives of Medical Sciences and Public Health, 2021)
Breast milk is an ideal source of nutrition because it is balanced in composition and meets the growing needs of the infant. Exclusive breastfeeding is a form of healthy behavior for infants. The research design is an analytical survey utilizing an explanatory research factors and the dependent variable of mother's willingness to breastfeed exclusively. The chi square test and logistic regression were used in this study's analysis. The results indicated that the chisquare test indicated that there is a relationship between predisposing and reinforcing factors and nursing mothers' willingness to breastfeed exclusively. There is no correlation between enabling factors and breastfeeding mothers' willingness to breastfeed exclusively. The result of the logistic regression test indicates that predisposing and reinforcing variables have an effect on nursing mothers' willingness to breastfeed exclusively. Predisposing variables are the most important factor affecting breastfeeding mothers' willingness to breastfeed exclusively. It is recommended that Polonia Puskesmas staff improve breastfeeding mothers' attitudes and motivation toward exclusive breastfeeding by counseling them on the importance of exclusive breastfeeding for infants during pregnancy and lactation.